WATER FOOTPRINT IN BRAZIL: STATE OF THE ART AND ITS INTERRELATIONS WITH AGRICULTURE AND THE ENVIRONMENT (Editora Impacto Científico, 2025)
The water footprint is a tool used to assess water needs for vegetables, water flows related to trade in these products and the amount of fresh water needed to dilute pollutants in the soil system. Therefore, the objective of this systematic review was to deepen the concepts of water footprint and the terms: blue water, green water, gray water and discuss solutions for water scarcity in the face of food production. The review was carried out through a systematic approach in three stages: step 1: Planning and formalization of the research via study formalization; Step 2: Execution of the research according to the study protocol; Step 3: Summarize the collected data. The articles were compiled from high impact databases such as: Pubmed, SciELO, Google Scholar, Science Direct, Scopus, Redalyc, Portal de Periódicos Capes, Latindex and Agris-FAO. The terms used in the search were: Water footprint and Water footprint. The parameters blue water, virtual water and gray water are the most frequently cited in the assessment of water sustainability in the regions and food production. Gray water was related to domestic effluents and water from solubilization of pollutants. In the case of semi-arid environments, gray water stands out as a tool of great importance in assessing sustainability and as a starting point for choosing species more adapted to climatic conditions with water deficit.DOI: https://doi.org/10.56238/edimpacto2025.090-042